Considering the Dark Side of Work: Bullshit Job Perceptions, Deviant Work Behavior, and the Moderating Role of Work Ethic - Johanna Riester; Johannes Keller (Journal of Business Ethics, 2024)
This contribution aims to expand the study of experiences at work by (a) analyzing a theoretical perspective concerning experiences at work which emphasizes both positive aspects as well as negative aspects, (b) exploring the relation of both negative (Bullshit job perceptions; BJP) and positive aspects (Meaningful Work perceptions; MWP) experienced at work to negative work-related behavior (Counterproductive Work Behavior [CWB] and Cyberloafing), (c) investigating the (moderating) role of work ethic, and (d) examining the robustness of these relations when considering additional contextual factors (organizational work values and tightness–looseness reflecting social norms). Three studies were conducted, including two samples of German employees ( N 0.167em=0.167em247 and N 0.167em=0.167em240), and another one of employees in the USA ( N0.167em =0.167em253). Our findings reveal that negative experiences at work (BJP) are the main predictor of problematic workplace behavior (CWB and Cyberloafing). Furthermore, their relation was contingent on individuals' endorsement of work ethic. BJP and CWB (or Cyberloafing) were more closely associated for individuals strongly endorsing work ethic. In contrast, the relation of positive experiences (MWP) to problematic behavior at work was not significantly qualified by work ethic. The observed relations were robust when additional contextual factors were controlled for. The results emphasize the importance and complexity of work experiences including and differentiating positive and negative aspects. They also highlight the significance of work ethic and related beliefs of employees in shaping problematic behavior in work settings.
Keywords: 300; Bullshit job perceptions; Meaningful work; Deviant work behavior; Work ethic